Innovation Village from Waste to Processed Products of Delicious and Nutritious Village Food Sukamanah, Megamendung District, Bogor Regency - Yuppy Triwidatin; Yulianingsih (Asian Journal of Community Services, 2022)
Starting from concerns about food waste and utilizing materials that are around, residents of Sukamanah Village, Megamendung District, Bogor Regency, through this community service dare to innovate by processing unused food ingredients into a type of product with high economic value. The existence of these innovation demands makes Sukamanah Village to have ideas that can be used in order to solve problems in Sukamanah Village in utilizing potential. The problem is that the number of edamame beans does not pass in the marketing. Community creativity is still low in utilizing raw materials from edamame nuts. Edamame beans that don't pass through sorting are mostly left alone. The selling value also tends to be low because they are only sold in the surrounding area or only consumed by themselves, compared to edamame beans that pass sorting and are marketed to supermarkets. If not processed properly, a lot of edamame beans will be wasted. So, this is where the need for an idea that can develop the potential of edamame beans. In general, the innovation of edamame bean ice cream is a form of utilization of edamame nuts that are sorted or do not meet the requirements to be marketed. In particular, edamame bean ice cream innovation aims to increase people's income and creativity. Edamame peanut ice cream innovation can make people become entrepreneurs.